Global corruption report : education - Transparency International (London : Earthscan, Publishing for a sustainable future, Routledge, Taylor & Francis Group, 2013)
"The Global Corruption Report (GCR) is Transparency International's flagship publication, bringing the expertise of the anti-corruption movement to bear on a specific corruption issue or sector. The Global Corruption Report on education and research consists of more than 50 articles commissioned from experts in the fields of corruption and education, from universities, think-tanks, business, civil society and international organisations"--
Includes bibliographical references and index.
Keywords: Education -- Corrupt practices -- Cross-cultural studies; Education -- Economic aspects -- Cross-cultural studies; Education and crime -- Cross-cultural studies; BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / Development / Sustainable Development; BUSINESS & ECONOMICS / Environmental Economics